2018
DOI: 10.18378/rvads.v13i3.5788
|View full text |Cite
|
Sign up to set email alerts
|

Abelhas e espécies melitófilas da mata ciliar do riacho Salgadeira, município de Alcantil, Paraíba

Abstract: A Caatinga encontra-se inserida no domínio intertropical e possui uma cobertura vegetal de formação xerofítica complexa. Sua degradação está contribuindo para o desaparecimento de espécies de plantas e animais. As abelhas, participam do processo de polinização, também se enquadram neste problema. Neste trabalho foram avaliadas a riqueza e abundância de abelhas em duas áreas de mata ciliar da Caatinga, nos trechos preservado e degrado (salinizado), do riacho Salgadeira. Nas áreas selecionadas foram coletadas ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
3
0
5
Order By: Relevance
“…The large representation of mainly nectariferous species reported in the present study corroborates the results obtained by Santos et al (2006b) in the Caatinga, as well as other studies in other vegetation types, such as Viana et al (2006) for restinga formations and Lopes et al (2016) for the Cerrado. For the latter studies, there might not be Regarding the species of Senna reported by us, Moura et al (2018) highlight that due to the genus' poricidal anthers, pollen is their only floral resource. The sharing of bee species between certain areas seems to indicate the existence of a foraging pattern between bee species, which includes Apis mellifera, that despite foraging a wide range of plants species, shows a clear preference for certain species in each area (Aguiar et al 2002;Pott & Pott 1986).…”
Section: Diversity Of the Bee Floramentioning
confidence: 79%
“…The large representation of mainly nectariferous species reported in the present study corroborates the results obtained by Santos et al (2006b) in the Caatinga, as well as other studies in other vegetation types, such as Viana et al (2006) for restinga formations and Lopes et al (2016) for the Cerrado. For the latter studies, there might not be Regarding the species of Senna reported by us, Moura et al (2018) highlight that due to the genus' poricidal anthers, pollen is their only floral resource. The sharing of bee species between certain areas seems to indicate the existence of a foraging pattern between bee species, which includes Apis mellifera, that despite foraging a wide range of plants species, shows a clear preference for certain species in each area (Aguiar et al 2002;Pott & Pott 1986).…”
Section: Diversity Of the Bee Floramentioning
confidence: 79%
“…Diversos levantamentos da apifauna na região semiárida do Nordeste brasileiro mostram a representatividade de A. mellifera e T. spinipes, sendo geralmente as espécies mais abundantes nesses estudos, tanto em áreas naturais quanto em áreas degradas, devido à grande capacidade de adaptação desses insetos em diferentes ambientes, o comportamento generalista na coleta de alimento e as colônias muito populosas (Pigozzo & Viana, 2010;Moura et al, 2018).…”
Section: Resultsunclassified
“…O maior número de pesquisas encontro é sobre as abelhas entre os grupos que constituem a guilda de antófilos na Caatinga (p.ex. AGUIAR; MARTINS, 1997;VIANA, 1999;MARTINS, 2003;ZANELLA, 2005;BATALHA FILHO et al, 2007;MILET-PINHEIRO;SCHLINDWEIN, 2008;PIGOZZO;VIANA, 2010, SILVA et al, 2012MOURA et al, 2018;SANTOS et al, 2020).…”
Section: Introductionunclassified